ANALISIS APLIKASI DAN PENERAPAN MATEMATIKA PADA ILMU EKONOMI FUNGSI PERMINTAAN DAN PENAWARAN - Br. Barus, Mika Debora; Azzahra, An Suci (Jurnal Akuntansi Bisnis dan Publik, 2020)
Mathematics is an abstract science whose reasoning is made as real. Mathematics is also the parent of other branches of science, especially in the field of Economics. Economic problems are very complex, this is due to the relationship between economic variables in the real world. It becomes a phenomenon to build an idea on the economic model by simplifying it based on mathematical science. The demand and supply function is one of the economic phenomena simplified into a mathematical economic model, namely by selecting two economic variables, namely the price variable and the variable number of goods a product is asked for by consumers or those offered by producers. To find out the mathematical relationship on the concept of economics, especially demand and supply is the purpose of this study. The method used in this research is exploratory. Research results obtained: (1) The relationship of demand and supply functions is built based on mathematical ideas by looking at variables based on the concept of linear functions, (2) demand and supply problems as well as market equilibrium of two kinds of products can also be built based on the mathematical concept of a two-variable linear equation system and the solution is built by the method of elimination, substitution, matrix, and graphics.